2011
DOI: 10.47893/ijmie.2011.1001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Analysis of Composite Leaf Spring under the Static Load Condition by using FEA

Abstract: Leaf springs are one of the oldest suspension components they are still frequently used, especially in commercial vehicles. The past literature survey shows that leaf springs are designed as generalized force elements where the position, velocity and orientation of the axle mounting gives the reaction forces in the chassis attachment positions. Another part has to be focused, is the automobile industry has shown increased interest in the replacement of steel spring with composite leaf spring due to high streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Patunkar et al [ 6 ] presented a comparison of a suspension system composed of glass fiber and steel leaf spring after carrying out their complete design and analysis using Pro-E ® and ANSYS 10.0 ® . The results presented in their research work showed that the deflection of the steel leaf spring was better than the composite leaf spring but at the cost of weight.…”
Section: Introductionmentioning
confidence: 99%
“…Patunkar et al [ 6 ] presented a comparison of a suspension system composed of glass fiber and steel leaf spring after carrying out their complete design and analysis using Pro-E ® and ANSYS 10.0 ® . The results presented in their research work showed that the deflection of the steel leaf spring was better than the composite leaf spring but at the cost of weight.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the stress, deflection, and weight reduction ratio analysis results to the current analytical and experimental solutions. Furthermore, composites are roughly 40% lighter than traditional steel leaf springs [8]. Dev dutt Dwivedi and V.K.Jain.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile over delayed load cycles and under compressive load increased the development of fatigue crack. 6 Fractography must be analyzed by the SEM technique for failure analysis. 7 The performance of vehicle components such as air suspension; it relates to vehicle safety.…”
Section: Introductionmentioning
confidence: 99%